Cooperation Methods Using in E-Learning for It Specialists' Competence Development - Gintaute-Marihina, Ruta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Today the daily life of the population is impossible without technology. As technology is constantly evolving, we need to provide ICT technology, computer networks and computer systems solution implementation, maintenance skills for future IT professionals. To find new ways of ICT professional competence to develop better and better as the professional competence more effective train. The study process main result is to prepare IT professionals with basic ICT competencies and skills that should be motivated and skilled for lifelong learning. Nowadays, still not used sufficiently effective e-learning technology options to achieve a better and more sustainable learning results. This paper describes a issue in which, contrary to traditional study process, students have opportunities to cooperate in a virtual environment using e-learning technologies, enhance your initial results of the work. The study process, using e-learning technology and cooperation methods was improved and developed IT specialists’ competencies and skills, which are important for computer systems and network administrator at work. Consequently, it was held IT competencies improvement, learning from each other.